The role of lenders' trust in determining borrowing conditions for sovereign debt: An analysis of one-period government bonds with default risk - Yanling Guo (Kiel Institute for the World Economy (IfW), 2015)
In this paper, the author considers the sovereign debt in the form of one-period government bonds with default risk, which can be purchased by and traded among domestic and foreign investors. She shows that the weight assigned to the lenders' interest by the borrowing government at the time of debt repayment, which captures the lenders' trust in the government's propensity to repay the debt and is denoted as », also determines the default risk: a higher » means a lower default risk ceteris paribus which leads to a lower risk premium, and vice versa. Since this relationship only holds in the "good equilibrium", the author further shows that the "good equilibrium" is the only stable equilibrium under some quite general assumptions while the "bad equilibrium" is an unstable one - a possible reason why in practice rather a negative correlation between » and the default risk as well as the corresponding risk premium is observed.
Keywords: F34; H63; H74; H62; H6; H87; 330; Public debt; sovereign debt; sovereign default; domestic debt; external debt; fiscal policy; government bond; government borrowing